2019
DOI: 10.5114/jcb.2019.85729
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry verification of 3D-printed individual template based on CT-MRI fusion for radioactive 125I seed implantation in recurrent high-grade gliomas

Abstract: Purpose: To verify the accuracy and efficacy of three-dimensional printing individual template (3D-PIT) with computed tomography-magnetic resonance imaging (CT-MRI) fusion for radioactive iodine-125 (125 I) seed implantation in high-grade brain gliomas. Material and methods: Between June 2017 and June 2018, 16 patients with recurrent high-grade gliomas (rHGG) underwent radioactive seed implantation with 3D-PIT. The prescribed dose was 120-140 Gy. We compared the dose distribution of the postoperative plan with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Liu et al . [ 9 ] investigated 16 patients with brain gliomas, and no difference was found between pre-operative and post-operative parameters. Besides, some scholars further confirmed that CT-guided RIS implantation assisted with 3D-PNCT was safe and effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al . [ 9 ] investigated 16 patients with brain gliomas, and no difference was found between pre-operative and post-operative parameters. Besides, some scholars further confirmed that CT-guided RIS implantation assisted with 3D-PNCT was safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…To further improve the accuracy of RIS implantation, Huang et al . were the first to employ three-dimensional printing non-coplanar template (3D-PNCT) for CT-guided RIS implantation in the treatment of head and neck tumor [ 6 ], and their results were proved safe, effective, and accurate [ 7 , 8 , 9 ]. However, few studies have compared dosimetric parameters of CT-guided RIS implantation assisted with and without 3D-PNCT.…”
Section: Purposementioning
confidence: 99%
“…35 Liu et al reported that in the treatment of recurrent high-grade gliomas, 3D-PIT based on CT/MRI fusion images can enable better positioning accuracy and dose distribution of radioactive I125 particle implantation. 36 Jiang et al studied the acute and late side effects of 3D- PNCT used in CT-guided radioactive I125 particles (RIS) implanted in recurrent cancer of the head and neck. Those authors found that 3D-PNCT-assisted RIS implantation can provide good positioning accuracy, and there were no obvious adverse reactions for locally recurring malignant head and neck tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Both computed tomography (CT) and magnetic resonance imaging (MRI) have deficiencies in facilitating target delineation for brain tumors. Our previous research registered CT-MRI fusion images into brachytherapy TPS and three-dimensional printing individual template (3D-PIT) to guide brachytherapy for the treatment of brain gliomas and metastases, and achieved good results [ 3 , 4 ].…”
Section: Purposementioning
confidence: 99%